The REASON EVIDENCE FOR DISCLIPINARY BREACH CANNOT BE USED AS EVIDENCE FOR VIOLATION OF THE LAW - klarisa, klarisa klarisa; Rustyadi, Dudut (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
There are 3 norms for doctors in carrying out their proffession. The norms in medical practice consists of ethical,disciplinary and the legal norms. The Indonesian Medical Disciplinary Honorary Council (MKDKI) is an institution that determines whether or not there are errors made by doctors and dentists in the application of medical and dental disciplines. The MKDKI only handles violations related to service standards, professional standards and the standard operating procedures for medical practice. Meanwhile, the errors based on legal terms can be caused by violations and intentional acts, the settlement process follows the criminal or civil justice system based on the case presented. There are similarities found between disciplinary and legal norms, which are both assess whether an act or action performed by a doctor is right or wrong in medical practicing. However, what is found to be interesting is that, whenever a doctor is found to be guilty by the MKDKI, which means evidence of violations of medical discipline is found, which includes violations of discipline, it cannot be used as an direct evidence in criminal and civil justice procedures to prove the doctor the guilty legally.